2021
DOI: 10.1021/acs.joc.1c01517
|View full text |Cite
|
Sign up to set email alerts
|

A General Method for α-Oxyacylation of Vinyl Ketones Using Koser’s Reagent

Abstract: A direct general method for the preparation of α-oxyacylated vinyl ketones using Koser's hypervalent iodine reagent is reported. A variety of acyloxy groups from long-chain aliphatic, aromatic, α,β-unsaturated carboxylic acids have been installed efficiently for the first time. The oxyacylated adducts were used for the preparation of densely functionalized chiral δ-lactones and cyclopentenes using carbene organocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In 2020, we reported the first umpolung Morita–Baylis–Hillman reaction and showed that it could be used to prepare 1,2-diones and 2-tosylenones. 23d , 25 It occurred to us that this novel concept could be useful for accessing 2-fluoroenones from ubiquitous enones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, we reported the first umpolung Morita–Baylis–Hillman reaction and showed that it could be used to prepare 1,2-diones and 2-tosylenones. 23d , 25 It occurred to us that this novel concept could be useful for accessing 2-fluoroenones from ubiquitous enones.…”
mentioning
confidence: 99%
“…In this context, we and others , have reported extensively on the chemistry of iodine­(III)–enolonium species, i.e., the electrophilic equivalent of classical lithium enolates. In 2020, we reported the first umpolung Morita–Baylis–Hillman reaction and showed that it could be used to prepare 1,2-diones and 2-tosylenones. , It occurred to us that this novel concept could be useful for accessing 2-fluoroenones from ubiquitous enones.…”
mentioning
confidence: 99%